POLITICAL TOLERANCE IN INDONESIAN-MUSLIM - Rena latifa; Melanie Nyhof; Muthia Rahmah; Abdul Rahman Saleh (Mimbar Agama Budaya, 2022)
Abstract  In the field of political behavior, tolerance is a crucial element to keep harmonious relationship. Studies should be able to measure a valid construct of tolerance in an effort to understand it further. Ferrar (1979) conducted a research focusing on the concept of political tolerance and theorized political tolerance to have three dimensions, namely flexible, approval, and allowance. This study aims to construct a political tolerance scale based on Ferrar’s concept and dimensions. Confirmatory Factor Analysis (CFA) is employed to test the construct validity and dimensionality of the Political Tolerance Scale. Participants were 300 Indonesian-Muslims. The results support the Political Tolerance Scale as a unidimensional scale consists of flexible, approval, and allowance dimensions. However, the limitation of the samples’ characteristic suggests future studies to conduct further researches on samples with different characteristics.AbstractDalam ilmu perilaku politik, toleransi adalah merupakan elemen penting untuk menjaga keharmonisan hubungan. Kajian saintifik harus mampu mengukur konstruk toleransi yang valid dalam upaya memahaminya lebih jauh. Ferrar (1979) melakukan penelitian yang berfokus pada konsep toleransi politik dimana toleransi politik diteorikan memiliki tiga dimensi, yaitu fleksibel, persetujuan, dan pengakomodiran. Penelitian ini bertujuan untuk mengkonstruksi alat ukur toleransi politik. Analisis faktor konfirmatori (CFA) digunakan untuk menguji validitas konstruk dan dimensi Skala Toleransi. Pesertanya adalah 300 orang Muslim Indonesia. Hasil yang didapat mendukung Skala Toleransi Politik sebagai skala unidimensional yang terdiri dari dimensi fleksibel, persetujuan, dan pengakomodiran. Namun, keterbatasan karakteristik sampel mendorong studi selanjutnya untuk melakukan penelitian lebih lanjut pada karakteristik sampel yang berbeda.